Firm Performance: A Longitudinal Study of Corporate Social Responsibility and its Societal Impact - Usman, Berto; Nurazi, Ridwan; Zoraya, Intan; Yennita (Thailand and The World Economy, 2024)
The goal of this study is to investigate how social impact, corporate social responsibility (CSR) reporting practices, and firm performance relate to one another in the context of ASEAN (Association of Southeast Asian Nations) banking. The sample was screened from 27 publicly listed banks in five ASEAN member countries (i.e., Indonesia, Malaysia, Singapore, the Philippines, and Thailand), with the period of observations ranging from 2011 to 2019 fiscal year. Social impact is a measure of social performance pillar scores provided by the ASSET4 CSR ranking companies. While, CSR reporting practices used three surrogate indicators: (i) the presence of CSR report; (ii) the existence of CSR assurance; and (iii) the adoption of the Global Reporting Initiatives (GRI) disclosure framework. Firm performance used accounting-based (i.e., return on asset and revenue) and market-based (i.e., market capitalization) measures. This study used longitudinal panel data analysis, including the fixed effect model with robust standard errors. The obtained empirical evidence shows that social impact is positively and significantly associated with three proxies of firm performance (ROA, REVENUE, and MCAP), while the proxies of CSR reporting practices show a partial positive and significant association with the proxies of firm performance. The additional analysis using lagged independent variables and an alternate measure of firm performance (ROE) shows slightly more consistent results relative to the main analysis, suggesting that firm performance needs some time lag so as to allow the impact of CSR reporting practices to be reflected in the variance of firm performance. The empirical tests using the ASEAN setting suggest that the idea of CSR has consistently evolved from being noticed as one of the detrimental factors to banks’ profitability to being deemed as one of the prerequisite conditions for gaining more potential benefits as strategic initiatives and objectives. Given that, banks should consider the importance of mandatory non-financial information publication to their stakeholders. This research paper advances the works of literature by enriching the limited empirical evidence in the context of social impact, CSR reporting practices, and firms’ performance in Non-Environmentally Sensitive Industries (NESIs). Apart from that, to the best of the authors’ knowledge, this is among the first studies that elaborate on the particular interplay between the so-called “social impact,” CSR reporting practices, and firms’ performance in ASEAN.